2015
DOI: 10.4049/jimmunol.1302456
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 Orchestrates Local Epigenetic Changes for Chromatin Accessibility and Rearrangements by Direct Binding to the TCRγ Locus

Abstract: The transcription factor STAT5, which is activated by IL-7R, controls chromatin accessibility and rearrangements of the TCRγ locus. Although STAT-binding motifs are conserved in Jγ promoters and Eγ enhancers, little is known about their precise roles in rearrangements of the TCRγ locus in vivo. To address this question, we established two lines of Jγ1 promoter mutant mice: one harboring a deletion in the Jγ1 promoter, including three STAT motifs (Jγ1PΔ/Δ), and the other carrying point mutations in the three ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Hence, both mice and humans with STAT5-associated deficiencies are severely immunocompromised (24,53). T cells of the γδ lineage are reduced in the thymus and lymphoid tissues of fully STAT5deficient mice (21), and this has been attributed to a failure to successfully rearrange the TCR early during embryonic development (26). However, our data show that γδT17 cells require STAT5 signaling to expand and survive after they exit the thymus.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Hence, both mice and humans with STAT5-associated deficiencies are severely immunocompromised (24,53). T cells of the γδ lineage are reduced in the thymus and lymphoid tissues of fully STAT5deficient mice (21), and this has been attributed to a failure to successfully rearrange the TCR early during embryonic development (26). However, our data show that γδT17 cells require STAT5 signaling to expand and survive after they exit the thymus.…”
Section: Resultsmentioning
confidence: 73%
“…However, there are currently no mechanistic data regarding their individual contribution in γδ T cell biology. One of the suggested mechanisms for the dependence of developing γδ T cell progenitors on STAT5 is its ability to induce TCRγ rearrangements, due to 3 highly interspecies-conserved inverted-repeat STAT5 consensus sites within the Tcrg locus (26).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, both mice and humans with STAT5-associated deficiencies are severely immunocompromized (Imada et al, 1998; Kofoed et al, 2003). T cells of the γδ lineage are reduced in the thymus and lymphoid tissues of full STAT5-deficient mice (Hoelbl et al, 2006), and this has been attributed to a failure to successfully rearrange the TCR early during embryonic development (Wagatsuma et al, 2015). However, our data show that γδT17 cells require STAT5 signaling to expand and survive after they exit the thymus.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently no mechanistic data regarding their individual contribution in γδ T cell biology. One of the suggested mechanisms for the dependence of developing γδ T cell progenitors on STAT5 is its ability to induce TCRγ rearrangements, due to three highly interspecies conserved inverted repeat STAT5 consensus sites within the TCRγ locus (Wagatsuma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies definitively demonstrated that the STAT5 hypomorph mice retained significant STAT5 function. Studies with STAT5 knockout mice demonstrated that STAT5 plays a critical role in the development of γδ T cells, as it regulates T-cell receptor (TCR) γ gene rearrangement 26, 27 . Likewise, STAT5 is required for expansion of double-negative thymocytes 25 .…”
Section: Stat5 In T-cell Developmentmentioning
confidence: 99%